2020
DOI: 10.3389/fpls.2020.588005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Manipulation in Irradiance Induces Oxidative Free-Radical Release in a Fast-Ice Algal Community (McMurdo Sound, Antarctica)

Abstract: Sea ice supports a unique assemblage of microorganisms that underpin Antarctic coastal food-webs, but reduced ice thickness coupled with increased snow cover will modify energy flow and could lead to photodamage in ice-associated microalgae. In this study, microsensors were used to examine the influence of rapid shifts in irradiance on extracellular oxidative free radicals produced by sea-ice algae. Bottom-ice algal communities were exposed to one of three levels of incident light for 10 days: low (0.5 μmol ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…An alternative to estimating primary production, as in a majority of studies, relies upon a radioisotope tracer to estimate the rate of carbon fixation by photosynthesis (i.e., 14 C) for samples of ice algae collected from a given point (ice core) location, after the sample has been removed from the sea ice environment. Measurements of production, the balance between respiration and photosynthesis at the community level (Rysgaard and Glud, 2004;Rysgaard et al, 2008), and algal stress (Kennedy et al, 2020) can also be assessed using in situ or in vivo O 2 -based technologies. These studies have shown net heterotrophic conditions (net O 2 uptake) during the initial spring bloom period in FYI due to high respiration (Campbell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to estimating primary production, as in a majority of studies, relies upon a radioisotope tracer to estimate the rate of carbon fixation by photosynthesis (i.e., 14 C) for samples of ice algae collected from a given point (ice core) location, after the sample has been removed from the sea ice environment. Measurements of production, the balance between respiration and photosynthesis at the community level (Rysgaard and Glud, 2004;Rysgaard et al, 2008), and algal stress (Kennedy et al, 2020) can also be assessed using in situ or in vivo O 2 -based technologies. These studies have shown net heterotrophic conditions (net O 2 uptake) during the initial spring bloom period in FYI due to high respiration (Campbell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The high accumulation of ROS generates oxidative stress [11]. ROS can induce DNA damage, protein oxidation, membrane lipid peroxidation and pigment destruction [2,6,12]. Therefore, a considerable amount of research has been conducted to explore the correlation between ROS scavenging and plant stress tolerance under extreme temperatures [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the consideration of a phytoplankton biomarker alongside IPSO25 helps to avoid the misinterpretation of the absence of the sea-ice biomarker in a sediment sample which may result from ice-free conditions or perennial sea ice and/or ice shelf cover, both conditions inhibiting any ice algae productivity (Lamping et al, 2021). Therefore, while the PIPSO25 index seems a promising tool, further investigations of other environmental parameters such as nutrient and light availability that affect bottom-ice algal growth (Kennedy et al, 2020), and of ice-shelf processes such as the formation and accretion of platelet ice that offer habitat to IPSO25-synthesizing diatoms, are required to obtain more information on the production and fate of IPSO25 and better constrain its applicability as an Antarctic sea-ice proxy (Lamping et al, 2021). Further attempts to calibrate the PIPSO25 index against observational (i.e., satellite) sea-ice data also require higher circum-Antarctic spatial coverage of HBI analyses conducted on well-dated, ideally by 210 Pb and 14 C, surface sediments.…”
Section: Highly Branched Isoprenoids (Hbis)mentioning
confidence: 99%